Immigrant Youth’s Perceptions of the Library: A Pilot Study Involving Youth Ages 14-18 years of African and Caribbean Origin - Artinger, Joseph; Rothbauer, Paulette M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
A pilot study of immigrant youth ages 14-18 of African and Caribbean descent revealed a generation wired to the internet for their information needs. The study finds that they would benefit from library programs better suited to their day to day life questions concerned with living in the adopted community. Une étude pilote auprès de jeunes de 14 à 18 ans d'origine afro-caribéenne révèle une génération qui se branche sur le web pour satisfaire ses besoins informationnels. L'étude démontre que ces jeunes tireraient profit de programmes en bibliothèque mieux adaptés aux enjeux du quotidien qui pavent leur vie dans une communauté d'adoption.